Nature and extent of damage by rice weevil, Sitophilus oryzae (L.) on different cereals - Haque, NM Mozaddedul; Haq, M; Karim, ANMR; Alam, MZ (University Journal of Zoology, Rajshahi University, 2007)
Key words: Sitophilus oryzae; grains; infestation; comparative infestibility; weight loss Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 27-30